Young rats with increased circulatory asymmetric dimethylarginine exhibited spatial deficit and alterations in dorsal hippocampus brain-derived neurotrophic factor and asymmetric dimethylarginine: Effects of melatonin. Issue 78 (November 2019) - Sheen, Jiunn-Ming; Yu, Hong-Ren; Tain, You-Lin; Chen, Yu-Chieh; Hsu, Mei-Hsin; Huang, Li-Tung
Highlights: Continuous ADMA infusion in young rats caused spatial deficit. Continuous ADMA infusion in young rats increased ADMA and decreased BDNF in the plasma and dorsal hippocampus. Melatonin alleviated spatial deficit and restored ADMA and BDNF the changes in plasma and dorsal hippocampus. Abstract: Increased plasma concentration of asymmetric dimethylarginine (ADMA) can be encountered in chronic inﬂammatory disease, liver damage, renal failure, and multiple organ failure. In addition, an association between circulating ADMA and all-cause mortality has been reported. Male Sprague-Dawley rats, postnatal day (PND) 17 ± 1, received continuous ADMA infusion via an intraperitoneal pump. Spatial performance, as well as plasma and dorsal hippocampus ADMA and brain-derived neurotrophic factor (BDNF) concentration, were examined and the effect of melatonin was tested. We found that a 4-week continuous ADMA infusion in young rats caused spatial deficit. Furthermore, increased ADMA concentration and decreased BDNF expression were found in the plasma and dorsal hippocampus. Melatonin protected against these effects, alleviating spatial deficit and reducing the changes in plasma and dorsal hippocampus ADMA and BDNF concentration.